Ferramentas de saúde móvel empregadas para melhorar a adesão ao tratamento do diabetes mellitus: uma análise comportamental - RossinI, Amanda Nunes (2023)
Adherence to diabetes mellitus treatment is extremely important to improve biological outcomes and the quality of life for people with the disease, but establishing these behaviors is a challenge. Some mobile technologies (mHealth) have been used in order to to facilitate communication with diabetic people, monitor data and provide educational information that can promote adherence. A systematic review of the literature involving 13 articles was carried out to assess the efficiency of mHealth tools on the adherence of people with diabetes mellitus and the feasibility of their use. Most of those tools used a biological measure as as indicator of adherence and did not observe the behavior directly. Self-report was also used for the same purpose. Studies that used complete contingencies had better results in comparison with incomplete contingencies’ studies. Furthermore, the studies that used two-way interactions had better results than the others. As the use of mHealth tools is under development, it is necessary to think about how to improve this type of intervention. More studies using complete contingencies and two-way interactions are recommended. It would also be interesting to enable the direct recording of behavior and consider that some people may not have access to mHealth tools